The temple of the new faith. Film images of the construction of the Palace of Culture 1952–1955 - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The first study of its kind, Marek Hendrykowski’s paper examines frame by frame the symbolic role of the construction of the Palace of Culture in the ideological context of the Stalinist period and its emergence into the realm of public discourse in the early 1950s.